Retention and Efficacy of Citizen Scientist Volunteers of the Texas Quail Index - Kelly S. Reyna; Dale Rollins (National Quail Symposium Proceedings, 2017)
The Texas Quail Index (TQI) was a 5-year, science-based project that utilized citizen scientists to collect data in the field, including 5 indices of bobwhite abundance in the spring, and 3 indices of bobwhite abundance in the fall. Over the course of the study, 84% of all volunteers dropped out of the program and <8% of all data sets were complete. Accordingly, we surveyed the volunteers by mail to determine the rate and cause of participation decline and to identify characteristics of a reliable volunteer. Results indicated that annual volunteer participation rate declined more rapidly as time and labor requirements increased. Similarly, 74.3% of survey respondents who dropped out of the study reported leaving because the project required too much time and work. Motives may have contributed to the volunteer attrition as 72% of volunteers joined the program to learn more about quail management; however 71% of those that left the program reported not gaining knowledge in that area. We recommend that project designs, for citizen-science projects, should incorporate the motives of volunteers and recruit those whose motives best align with project goals. We also recommend that citizen-science coordinators keep volunteer tasks short and within the interest of the volunteer, to increase retention. Finally, we recommend stipends for volunteers on large-scale, laborious projects.
Keywords: citizen science; Colinus virginianus; management; motives; northern bobwhite; project design; quail abundance; Texas; volunteers